The impact of computer_mediated immediate feedback on developing oral presentation skills: An exploratory study in virtual reality - Stan Van Ginkel; Dominic Ruiz; Asko Mononen; Cendel Karaman; Ander de Keijzer; Jirarat Sitthiworachart (My University, 2020)
Abstract Feedback plays a central role in learning. Crucial to this is the nature and timing of the feedback. This experimental study explores the efficacy of immediate computer‐mediated feedback within a virtual reality environment designed to facilitate the development of pre‐university students' presentation skills. Two conditions were established to assess the efficacy: immediate computer‐mediated feedback; a control condition of delayed expert‐mediated feedback. Results showed improvement but no statistically relevant difference in performance gains between the two conditions, suggesting both can facilitate learning. Furthermore, students perceived the environment to be an effective and motivating platform in which to practise presentation skills. For educators seeking viable alternatives to face‐to‐face presentation practice and feedback, the finding that immediate computer‐mediated feedback is potentially as effective in aiding presentation performance is crucial for two reasons: first, it expands practice opportunities for students; second, it could result in less pressure on resources, including time and staffing.
Keywords: Presentation (obstetrics); Staffing; Computer-Assisted Instruction; Exploratory research; Student Assessment and Feedback